Repellency of Tribolium castaneum Herbst and Tribolium confusum Duval (Coleoptera : Tenebrionidae) to the Rhizome and Leaf Extracts of Zingiber cassumunar Roxb. - Khanam, LAM; Rahman, MS; Mahfuz, I (Bangladesh Journal of Scientific and Industrial Research, 2008)
Repellent activity of different solvent extracts of Zingiber cassumunar rhizome and leaf against Tribolium castaneum and T. confusum were conducted. The results indicated that both the insect species were repelled by Z. cassumunar rhizome and leaf extracts. Among these, acetone extracts of rhizome showed highest repellency to T. castaneum than those of other extract tested. Petroleum ether extracts of Z. cassumunar leaf acted as repulsive to T. castaneum whereas other extracts exhibited weak to moderate effects to the beetles. All the extracts of leaf produced weak to moderate effects to T. confusum however, methanol extract of leaf showed little effect to the bettles. Key words: Zingiber cassumunar, Seed and leaf extracts, Repellency, Tribolium castaneum, T. confusum. DOI: 10.3329/bjsir.v43i2.969 Bangladesh J. Sci. Ind. Res. 43(2), 251-258, 2008